Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 7 - Section 7.1 - Rational Expressions and Their Simplification - Exercise Set - Page 492: 70



Work Step by Step

Simplifying Rational Expressions 1. Factor the numerator and the denominator completely. 2. Divide both the numerator and the denominator by any common factors. --- Numerator = difference of squares = $(x+2)(x-2)$ Denominator = $-(x-2)$ Expression = $\displaystyle \frac{(x+2)(x-2)}{ -(x-2)}$ ... divide both with the common factor: $(x-2)$ Expression = $\displaystyle \frac{x+2}{-1}$ = $-(x+2)$ = $-x-2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.